Photosynthetic response of sweet potato (Ipomoea batatas) to photon flux density and elevated carbon dioxide - VELUMANI, RAVI; RAJU, SARAVANAN; GANGADHARAN, BYJU; K, PALLAVI NAIR; GEORGE, JAMES (The Indian Journal of Agricultural Sciences, 2017)
The continuous rise in the atmospheric CO2 due to anthropogenic activities is likely to benefit crop species with C3photosynthetic pathway by enhancing photosynthetic efficiency and crop productivity. This is particularly importantin the context of climate change and food security of ever increasing population amidst scarcity of natural resources.In the search of photosynthetically efficient climate smart genotypes. In the present study, the net photosynthetic rate(Pn), stomatal conductance (gs) and intercellular CO2 (Ci) was studied in twelve contrasting sweet potato genotypes,viz. Sree Arun, Sree Badhra, Sree Kanaka, Kanhangad, Pusa Safed, Pusa Red, Kisan, Gouri, Sankar and ST-13, S-1464and S-1466 under ambient (400 ppm) and eCO2 (eCO2) (600, 800 and 1000 ppm) and the Pn at photosynthetic photonflux densities (PPFDs), viz. 200, 400, 600, 800, 1000, 1200 and 1500 μmol/m2/h at 30oC and 400 ppm CO2 usingportable photosynthesis system. The maximum Pn of ten sweet potato genotypes was recorded at PPFD of 1500μmol/m2/s and the increase in Pn at PPFDs above 1000 μmol/m2/s were insignificant. The Pn steadily increased dueto short-term (ten minutes) exposure at eCO2 concentrations between 400 ppm and 1000 ppm in twelve sweet potatogenotypes. The sweet potato genotypes had the average Pn of 26.30, 33.41, 38.02 and 40.32 μmol/m2/s at 400, 600,800 and 1000 ppm CO2 respectively. However, the per cent of increment in Pn at eCO2 significantly declined (average5.98%) at CO2 concentrations above 800 ppm. The genotypes Gouri, Sankar, Sree Arun, and S1466 had 61.00 – 74.3%hike in Pn at eCO2 (1000 ppm) as compared to ambient CO2 (400 ppm). The per cent increment in Pn significantlydecreased at CO2 concentrations above 600 ppm. The differences in Pn were statistically significant across sweetpotato genotypes and CO2 concentrations (P>0.001), whereas the Pn had a quadratic relation with the increase inCO2 concentration (R2=0.603). The gs steadily decreased at eCO2 concentrations. The sweet potato genotypes hadthe average gs of 0.606, 0.508, 0.431, 0.376 mol H2O/m2/s at 400, 600, 800 and 1000 ppm CO2 respectively. Theper cent of decrease in gs at eCO2 significantly increased (average 38.33%) at 1000 ppm CO2. The differences ings were statistically significant across sweet potato genotypes and CO2 concentrations (P>0.001). The sweet potatogenotypes had the average Ci of 271.50, 405.20, 543.00, and 684.00 μmol CO2/mol air at 400, 600, 800 and 1000ppm CO2 respectively. However, the per cent of increment in Ci at eCO2 significantly declined (average 25.70%) atCO2 concentrations above 600 ppm. The differences in Ci were statistically significant across sweet potato genotypesand CO2 concentrations (P>0.001), whereas the Pn had a quadratic relation with the increase in Ci (R2=0.504). Theinteraction effect of genotypes and CO2 concentration on Ci, Pn and gs was insignificant. The differences in the totalchlorophyll and protein content in the leaves of sweet potato genotypes were statistically significant. Nevertheless,the gas exchange parameters were not influenced by the total chlorophyll and protein content.